2018
DOI: 10.1590/s1413-41522018136152
|View full text |Cite
|
Sign up to set email alerts
|

Fertirrigação do milho com água residuária sanitária tratada: crescimento e produção

Abstract: RESUMO Avaliou-se o crescimento vegetativo e a produção de milho em campo, fertirrigado com diferentes doses de água residuária da estação de tratamento de esgoto de Janaúba, Minas Gerais. Utilizou-se o delineamento em quatro blocos casualizados com parcelas subdivididas, sendo cinco tratamentos: água limpa + adubação mineral; e água residuária tratada equivalente a 50; 100; 150 e 200% da adubação com 60 kg.ha-1 de K2O em cobertura. Nas subparcelas, avaliaram-se as plantas aos 24, 38, 51 e 74 dias após a emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
5
0
6
Order By: Relevance
“…é uma cultura onde seu cultivo pode ser facilmente feito em vasos, a variedade de espécies de caládio no mundo é bem significante, apresentando assim vários tipos de cultivos. A prática do uso de fertirrigação com águas residuárias é apresentado em diversos estudos (CONDÉ et al, 2013;ALVES et al, 2018;MATOS et al, 2014). Diante do exposto o presente trabalho objetivou-se analisar as melhores porcentagens de diluições do uso da água residuária e varação de bulbo para produção de massa seca da parte área no cultivo do caládio (Caladium spp.…”
Section: Congresso Norte Nordeste De Ciências Agrárias (Online) -Avanço Tecnológico E Sustentabilidade Resultados E Discussõesunclassified
See 1 more Smart Citation
“…é uma cultura onde seu cultivo pode ser facilmente feito em vasos, a variedade de espécies de caládio no mundo é bem significante, apresentando assim vários tipos de cultivos. A prática do uso de fertirrigação com águas residuárias é apresentado em diversos estudos (CONDÉ et al, 2013;ALVES et al, 2018;MATOS et al, 2014). Diante do exposto o presente trabalho objetivou-se analisar as melhores porcentagens de diluições do uso da água residuária e varação de bulbo para produção de massa seca da parte área no cultivo do caládio (Caladium spp.…”
Section: Congresso Norte Nordeste De Ciências Agrárias (Online) -Avanço Tecnológico E Sustentabilidade Resultados E Discussõesunclassified
“…Rezende (2010), afirma que o capim-Mombaça é considerado uma das forrageiras tropicais mais produtivas e promissoras à disposição dos pecuaristas, podendo atingir anualmente, 33 t / ha de massa seca. Para isso, segundo Araújo et al (2018)…”
Section: Introductionunclassified
“…Table 7, it was found that the quantities of nutrients added to the soil in T 3 are greater than the crop requirements for P, Mg, Mn, Zn and Cu in the two cycles of cultivation, besides providing quantities exceeding 90% of the needs for N and Ca, greater than 70% of the requirements for K and greater than 50% of the requirements for Fe, in the two cultivation cycles. In the literature, there are several studies indicating the potential of TDE in providing significant amounts of organic matter and nutrients such as P, K, Ca and Mg to the soil, especially in soils with more clayey texture (Damasceno, Andrade, Gheyi, Dias, & Silva, 2011;Fortes et al, 2013;Alves, Santos, Kondo, Araújo, & Oliveira, 2018), and it may even meet 100% of the nutritional requirements of the cotton crop, thus replacing conventional fertilization, as reported by Sousa et al (2012). Thus, the use of treated domestic effluents plays a fundamental role in the planning and sustainable management of water resources, as it allows the sources of good quality water to be used for public supply and other priority uses (Lunardi & Rabaiolli, 2013).…”
Section: (Equation 4)mentioning
confidence: 99%
“…Maize cultivation in the Brazilian semi-arid region stands out for its economic importance in family farming, with a high contrast in yield due mainly to climatic conditions, irrigation and fertilization practices [1,2]. Due to water scarcity in the region, the use of wastewater for irrigation is a promising alternative for reducing the consumption of higher-quality water and hence reducing environmental How to cite: Almeida, T.A.B., M ontenegro, A.A.A., de Carvalho, A.A. and Tabosa, J.N., Soil and crop spatial variability in maize irrigated with domestic effluent.…”
Section: Introductionmentioning
confidence: 99%